Comparison study on hyaline cartilage versus fibrocartilage formation in a pig model by using 3D-bioprinted hydrogel and hybrid constructs - Sardroud, Hamed Alizadeh; Dos Santos Rosa, Gustavo [UNESP]; Dust, William; Cham, Tat-Chuan; Roy, Gwen; Bater, Sarah; Chicoine, Alan; Honaramooz, Ali; Chen, Xiongbiao; Eames, B Frank (IOP Publishing, 2024)
Cartilage tissue engineering (CTE) with the help of engineered constructs has shown promise for the regeneration of hyaline cartilage, where fibrocartilage may also be formed due to the biomechanical loading resulting from the host weight and movement. Previous studies have primarily reported on hyaline cartilage formationin vitroand/or in small animals, while leaving the fibrocartilage formation undiscovered. In this paper, we, at the first time, present a comparison study on hyaline cartilage versus fibrocartilage formation in a large animal model of pig by using two constructs (namely hydrogel and hybrid ones) engineered by means of three-dimensional (3D) bioprinting. Both hydrogel and hybrid constructs were printed from the bioink of alginate (2.5%) and ATDC5 cells (chondrogenic cells at a cell density of 5 × 106cells ml-1), with the difference in that in the hybrid construct, there was a polycaprolactone (PCL) strand printed between every two bioink strands, which were strategically designed to shield the force imposed on the cells within the bioink strands. Both hydrogel and hybrid constructs were implanted into the chondral defects created in the articular cartilage of weight-bearing portions of pig stifle joints; the cartilage formation was examined at one- and three-months post-implantation, respectively, by means of Safranin O, Trichrome, immunofluorescent staining, and synchrotron radiation-based (SR) inline phase contrast imaging microcomputed tomography (inline-PCI-CT). Glycosaminoglycan (GAG) and collagen type II (Col II) secretion were used to evaluate the hyaline cartilage formation, while collagen type I (Col I) was used to indicate fibrocartilage given that Col I is low in hyaline cartilage but high in fibrocartilage. Our results revealed that cartilage formation was enhanced over time in both hydrogel and hybrid constructs; particularly, the hydrogel construct exhibited more cartilage formation at both one- and three-months post-implantation, while hybrid constructs tended to have less fibrocartilage formed in a long time period. Also, the result from the inline-PCI-CT revealed that the inline-PCI-CT was able to provide not only the information seen in other histology images, but also high-resolution details of biomaterials and regenerating cartilage. This would represent a significant advance toward the non-invasive assessment of cartilage formation regeneration within large animal models and eventually in human patients.